Maternal Cytokines CXCL12, VEGFA, and WNT5A Promote Porcine Oocyte Maturation via MAPK Activation and Canonical WNT Inhibition - Liu, Xin; Hao, Yuchen; Li, Zhekun; Zhou, Jilong; Zhu, Hongmei; Bu, Guowei; Liu, Zhiting; Hou, Xudong; Zhang, Xia; Miao, Yi-Liang (Frontiers in Cell and Developmental Biology, 2020)
Maternal regulatory factors endow the oocyte with developmental competence in vivo, which might be absent in current in vitro maturation (IVM) systems, thereby compromising oocyte quality. In the present study, by employing RNA sequencing data analysis, we expect to identify potential contributing factors to support porcine oocyte maturation through binding to their receptors on the oolemma. Here, C-X-C motif chemokine ligand 12 (CXCL12), vascular endothelial growth factor A (VEGFA), and Wingless-type MMTV integration site family member 5A (WNT5A), termed CVW, are selected and confirmed to be important maternal cytokines for porcine oocyte maturation. Combined supplementation of CVW promotes the nuclear maturation percentage from 57.2% in controls to 75.9%. More importantly, these maternal cytokines improve the developmental potential of matured oocytes by parthenogenesis, fertilization, and cloning, as their blastocyst formation efficiencies and total cell numbers are increased. CVW supplementation also enlarges perivitelline space and promotes cumulus expansion, which results in a more complete transzonal projection retraction on the zona pellucida, and a reduced incidence of polyspermy in fertilized oocytes. Meanwhile, inhibiting the CVW receptor-mediated signaling pathways severely impairs oocyte meiotic resumption and cumulus expansion during IVM. We further determine that maturation improvement by CVW is achieved through activating the MAPK pathway in advance and inhibiting the canonical WNT pathway at the end of the IVM period. These findings provide a new combination of three cytokines to promote the porcine IVM process, which also holds potential to be used in human assisted reproduction technologies as well as in other species.